An analysis of raining and rewards factors on the reengineering process as implemented in Telcomm - Ali, Mass Hareeza (The Journal of Human Resource and Adult Learning, 2011)
The research focuses on the training and reward as factors on the implementation of reengineering in one of the telecommunication industry in Malaysia. The real name of the organisation had been disguised. The view and perception of employees of the organisation are presented in the form of data gathered through questionnaires. Information concerning particular aspects of training and rewards was included. This study will analysed the factor of training and rewards within the organisations during the implementation of business process reengineering (BPR) take place in that particular organisation. Results from the research were expected to contribute new information in the development criteria and things to be concerned of any implementation within training and rewards in Malaysia telecommunication sector.